Práticas de educação em saúde para a pevenção da cárie dentária : um estudo qualitativo - Garcia, Laíse Cecote (2016)
Dental caries is a highly prevalent disease worldwide, causing negative impact on quality of life of individuals. The decrease in the high cost of treatment, as well as the prevalence of this disease, it is possible by means of effective prevention and health promotion. The objective of this study was to identify the perception of dentists in the Unified Health System belonging to the 15th Regional of Health of Paraná as the health education practices for preventing tooth decay by means of a qualitative research. For this study was carried out the analysis of a database composed of interviews with 18 Dental Surgeons (CDs) active in the municipalities of the 15th Regional of Health of Paraná. Interviews were conducted face to face, based on a semi-structured and written script. The transcript of the recordings was done manually and the lines were categorized according to the method of content analysis proposed by Bardin, using the Atlas.ti 7.0 software. CDs reported doing health education practices, demonstrating an understanding of the importance of these activities. The strategies used were the transmission of information, demonstration of brushing techniques for self-care, understanding the importance of motivation and persistence for an effective result of the educational process, and the use of interactive methods to improve communication with the community. However, it was observed that there is still a partial understanding of the educational process, in varying degrees of understanding of the potential of educational activities, it is necessary to overcome the hegemonic model based on the transmission of information, a challenge to be overcome by the professionals and the community. The development of skills and competencies in communication at the undergraduate and graduate levels are needed, as well as the training of professionals in health care, for a performance with effectiveness in health education activities, aiming at a more conscious and healthy population.